Life and Death of an Egg Hunter: Proposal for a Reinterpretation of a Rapa Nui (Easter Island) String Figure Chant - de Laat, Mary (Waka Kuaka, 2019)
Pre-missionary Rapa Nui (Easter Island) literature has only survived in a small corpus of poorly understood recitations. Their obscurity has been attributed to the disappearance of the old culture as a result of the catastrophic decline of the native population in the second half of the nineteenth century and the considerable change that the Rapanui language has undergone under the influence of other languages. A similar judgement has been passed on one of the most popular songs in the traditional repertoire, a string figure chant that was recorded in the twentieth century by several anthropologists, among them Routledge in 1914 and Métraux in 1934–1935. A complete version of the chant was first published in 1960 by Barthel. However, his uneven translation takes many liberties with the original text and leaves much unexplained. Barthel’s idea that the chant’s main topic is the burial of a man who once held the important ritual position of “birdman” has nevertheless been generally accepted by subsequent researchers. Fortunately, since then the unpublished fieldnotes of both Routledge and Métraux have become available. Despite the fact that they reveal that already in the first half of the twentieth century the chant’s meaning could no longer be explained by the native informants, they shed light on a number of cryptic passages by providing important material for comparison and reconstruction. This has made it possible to propose in this study an alternative interpretation of the text as a lyrical account of the death of a hopu manu, a contender in the annual competition for the sacred bird egg to select the new birdman. If this proves to be correct, the chant would constitute a unique example of early Rapanui poetry, an intriguing artefact of the enigmatic birdman cult and an incentive for further research into texts that have been written off as too archaic and obscure.